The gold crusades : a social history of gold rushes, 1849-1929 - Fetherling, George, 1949- (University of Toronto Press, 1997)
"Among the hordes of starry-eyed 'argonauts' who flocked to the California gold rush of 1849 was an Australian named Edward Hargraves. He left America empty-handed, only to find gold in his own backyard. The result was the great Australian rush of the 1850s, which also attracted participants from around the world. A South African named P.J. Marais was one of them. Marais too returned home in defeat - only to set in motion the diamond and gold rushes that transformed southern Africa. And so it went."--Publisher's description.